National Gymnastics Judges Assoc., Inc.
1997 FIG Code of Points Update - March 15, 1999, in English. (In HTML format, original from Hardy Fink.) 1997 FIG Code of Points Update - March 15, 1999 en Español. Actualizaciones al Código de Puntuación de 1997 - Sumario completo al 15 de Marzo de 1999. (In Microsoft Word format, translated by Julio Marcos, VP-FIG Technical Committee.) Evaluation of elements submitted for the 1999 World Championships in English. These elements were evaluated and given difficulty values by the Men's Technical Committee, October 7, 1999, at the recent World Championships. (In HTML format, original from Hardy Fink.) Pommel Horse - Cross Travel Variations - August 29, 1997 In order to help prepare the judges on pommel horse at the World Championships, Mr. Istvan Karacsony, MTC-FIG, prepared this diagram to describe the various pommel horse cross travel variations and their relation to each other in terms of repetition. While this is an unofficial paper (as per Mr. Hardy Fink, President-MTC,FIG) it is a useful study aid to help judges understand the application of the repetition rules on cross travels. For a complete understanding of cross travels, you must refer to the Code of Points. Latest USA Judging Materials 97 Code Additional Interpretations #19a June 22, 1999, in HTML Format. This is the latest set of the NGJA's Additional Interpetations which supplement the FIG Code of Points. These interpretations are in effect immediately for the USA season. This set of Interpretations is an OFFICIAL NGJA document. Men's National Team Program 1999 Bonus Point System The following bonus point system was adopted by the Men's Program Committee on December 4, 1998, and will be used at the 1999 Winter Cup Challenge, the qualifying competition to the 1999 USA Championships, the 1999 USA Championships, and the 1999 World Championships Team Trials. The bonus points are awarded as extra points and do not come out of any other judging category. In no case may a gymnast receive a total score of greater than 10.0. This article resides on the USA Gymnastics web site. You will be leaving www.ngja.org NCAA99 Update #2, March 20, 1999 provides for those differences from the FIG and USA Interpretations that are specific to the NCAA program only. These updates are valid for all NCAA competitions. 1998-99 NCAA Modifications to the Code of Points These are the 1998-1999 Official NCAA Gymnastics Rules, defining meet organization, scoring procedures, appropriate judging and evaluation procedures, etc. Also included in the NCAA Rules is the NCAA Vault Value Table. 1997 F.I.G. Vaulting Table, v.1.06 (September 5,1999) (Acrobat Format) Vault 3310 corrected to match Code with 1/4 turn rather than 5/4 turn. Vault 3428 corrected to match the Code at 9.5 (handspring sideways w 1/4 turn and salto stretched). This table, prepared by Ken Achiron, lists the FIG Values along with the updated vault numbers for the vaults as listed in the new Code. The table is in Adobe Acrobat format. The table also has references to the JO exceptions and certain additional values for NCAA competitions.. A National Course Refresher for 1999-2000 This powerpoint presentation, created by Ken Achiron, Region Technical Director - East, is a review and refresher on the rules for 1999-2000, including the current NGJA and NCAA rules for this year. As a review, all material is unofficial Updated Junior Program Materials JO Course Notes 1997-2000, v.3.01 (September 5, 1999) (Acrobat Format) These are the NGJA's notes for judges on the Boys JO Program, prepared by Ken Achiron. These are practical sheets judges can use while on the floor at a J.O. competition. The Vault Table listed above is included in the packet. This set incorporates the changes of USAG's Update 6. All judges should purchase the official, USAG Junior Olympic Program manual from USA Gymnastics. Special: Men's Code of Points: Alternative Ways to Provide Stable Rules This article was produced for the 1998 FIG Congress and represents the USA Position regarding the Code of Points and its future direction. It is reproduced here in English, French, and Spanish. Men's Code of Points: Alternative Ways to Provide Stable Rules By Ron Galimore, John Scheer, Mark Graham, Butch Zunich, Harry Bjerke, Ken Allen, and Les Sasvary, 24 May, 1998. Routines.xls - Excel 4.0 Spreadsheet This file is a layout for creating tables describing men's gymnastics routines, with built in functions for validating your listings. The file contains previously created tables for examples, along with a readme for directions.